1184. A Phase 3, Multicenter, Randomized, Double-blind Study to Evaluate the Interchangeability of V114 and Prevnar 13™ with Respect to Safety, Tolerability, and Immunogenicity in Healthy Infants (PNEU-DIRECTION). (4th December 2021) - Bili, Adroniki; Dobson, Scott; Quinones, Jeffrey; Phongsamart, Wanatpreeya; Oberdorfer, Peninnah; Kosalaraksa, Pope; Dagan, Ron; Wilck, Marissa B; Vallejos, Waldimir; Nunn, Christine; McFetridge, Richard; Fu, Rong; et al.
Abstract: Background: Pneumococcal diseases (PD) caused by Streptococcus pneumoniae are a major health concern globally. In children, currently licensed pneumococcal conjugate vaccines (PCVs) provide protection against PD from vaccine serotypes, but other non-vaccine serotypes have emerged and contribute to most residual disease. V114 is a 15-valent investigational PCV containing serotypes 22F and 33F in addition to the 13 serotypes shared by Prevnar 13 TM (PCV13). This phase 3 study evaluated safety and immunogenicity of mixed PCV13/V114 regimens when changing from PCV13 to V114 at doses 2, 3, or 4. Methods: In this double-blind trial, 900 infants were randomized in equal ratios to five treatment groups using a 3 + 1 immunization schedule (3-dose infant primary series followed by one toddler dose). Groups 2, 3, and 4 started with PCV13 and switched to V114 at doses 4, 3, and 2, respectively. Groups 1 and 5 received four doses of PCV13 and V114, respectively. Immunoglobulin G (IgG) responses to the 15 pneumococcal serotypes in V114 were measured at 30 days post-dose 3, prior to dose 4, and 30 days post-dose 4 (PD4). Primary immunogenicity analysis was based on 13 shared serotype responses at PD4. Safety was evaluated as the proportion of participants with adverse events (AEs). Results: At 30 days PD4, IgG geometric mean concentrations (GMCs) for the 13 shared serotypes were generally comparable between V114/PCV13 mixed regimens (Groups 2-4) and participants that received the 4-dose PCV13 regimen (Group 1). Additionally, IgG GMCs for the 13 shared serotypes were generally comparable for participants that received the 4-dose V114 regimen (Group 5) and participants that received the 4-dose PCV13 regimen (Group 1). Infants given at least one dose of V114 mounted immune responses to two unique serotypes in V114 (22F and 33F). Frequency of injection-site and systemic AEs among study participants were generally comparable across all study groups. Conclusion: V114 was well tolerated with a generally comparable safety profile to PCV13. For the 13 shared serotypes, both mixed-dose and 4-dose regimens of V114 induced generally comparable antibody responses to a PCV13 4-dose regimen. Study results support interchangeability of V114 with PCV13 in infants. Disclosures: Adroniki Bili, MD, Merck & Co., Inc. (Employee, Shareholder) Ron Dagan, MD, Medimmune/AstraZeneca (Grant/Research Support, Scientific Research Study Investigator, Research Grant or Support)MSD (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Research Grant or Support, Speaker's Bureau)Pfizer (Consultant, Grant/Research Support, Scientific Research Study Investigator, Advisor or Review Panel member, Research Grant or Support, Speaker's Bureau) Marissa B. Wilck, MD, Merck & Co., Inc. (Employee, Shareholder) Waldimir Vallejos, MD, Merck & Co., Inc. (Employee, Shareholder) Christine Nunn, MS, Merck & Co., Inc. (Employee, Shareholder) Richard McFetridge, B.S., Merck & Co., Inc (Employee) Rong Fu, PhD, MSD China (Employee, Shareholder) Robert Lupinacci, M.S, Merck & Co., Inc (Employee, Shareholder) Luwy Musey, MD, Merck & Co., Inc. (Employee) Kara Bickham, MD, Merck Sharp and Dohme (Employee, Shareholder)